PENERAPAN SISTEM AKUNTANSI KEUANGAN PEMERINTAH DAERAH di BPKAD PROVINSI JAWA TENGAH - Iin Indarti; Retno Ginanjar; Wenny Ana Adnanti; Tjandra Tirtono (Jurnal Akuntansi dan Bisnis, 2024)
The purpose of this research is to examine the implementation of the Regional Financial Accounting System BPKAD of Central Java Province based on the quality of the Central Java Provincial Government’s financial reports, the Regional Financial Accounting System and the internal control of the Regional Government of Central Java Province. The Regional Financial and Asset Management Agency (BPKAD) of Central Java Province was formed based on the Regional Regulation of the Province of Central Java Number 9 of 2022 dated 9 November 2022 concerning the Formation and Composition of Regional Apparatus of the Province of Central Java and Governor Regulation Number 82 of 2022 dated 15 December 2022 concerning Organization and Administration of Regional Financial and Asset Management Agency of Central Java Province. The respondents in this study were employees or staff in the finance or accounting department at SKPD Central Java Province as many as 48 respondents. The results of this study, the suitability of the Financial Accounting System with the Financial Accounting Standards, obtained an average respondent’s answer of 4.4166, which means that the suitability of the Financial Accounting System with Financial Accounting Standards is good. Accounting recording procedures with Financial Accounting Recording with 4 question items, 48 ​​respondents also gave good answers, with an average answer of 4,6666. The making of periodic reports of Financial reports from 48 respondents with 4 question items also gave good results, with an average of 4.5103 respondents’ answers. The description of the quality of the financial statements is also good viewed from a reliable, relevant, understandable, and comparable perspective because the average respondent’s answer is 4,171 with 11 question items